Contrasting patterns of selection and drift between two categories of immune genes in prairie‐chickens. Issue 24 (7th December 2015) - Bateson, Zachary W.; Whittingham, Linda A.; Johnson, Jeff A.; Dunn, Peter O.
Abstract: Immune‐receptor genes of the adaptive immune system, such as the major histocompatibility complex (MHC), are involved in recognizing specific pathogens and are known to have high rates of adaptive evolution, presumably as a consequence of rapid co‐evolution between hosts and pathogens. In contrast, many 'mediating' genes of the immune system do not interact directly with specific pathogens and are involved in signalling (e.g. cytokines) or controlling immune cell growth. As a consequence, we might expect stronger selection at immune‐receptor than mediating genes, but these two types of genes have not been compared directly in wild populations. Here, we tested the hypothesis that selection differs between MHC (class I and II) and mediating genes by comparing levels of population differentiation across the range of greater prairie‐chickens ( Tympanuchus cupido ). As predicted, there was stronger population differentiation and isolation by distance at immune receptor (MHC) than at either mediating genes or neutral microsatellites, suggesting a stronger role of local adaptation at the MHC. In contrast, mediating genes displayed weaker differentiation between populations than neutral microsatellites, consistent with selection favouring similar alleles across populations for mediating genes. In addition to selection, drift also had a stronger effect on immune receptor (MHC) than mediating genes as indicated by the stronger decline of MHC variation in relation to population size. This is the first study in the wild to show that the effects of selection and drift on immune genes vary across populations depending on their functional role.